Les récits de résurrection des morts dans le Nouveau Testament - Rochais, Gérard (Cambridge Cambridge University Press, 1981)
The New Testament narratives reporting the resuscitation of dead persons by Jesus and Peter are discussed in detail in this monograph, and their theology is examined. The author compares the NT stories with the resuscitation episodes in the OT, and also with the broader category of NT miracle stories. This enables him to identify the features peculiar to the NT resuscitation accounts. Dr Rochais' analysis, using redaction-critical methods, demonstrates different stages in the formulation of the narratives, and attempts to identify the events or purposes underlying them. He makes reference to the development of Christology and the evolution of belief in the resurrection of the dead within the primative church, as well as to the theological positions of each of the evangelists. His analysis leads the author to the hypothesis that neither Jesus nor Peter in fact brought the dead to life. Dr Rochais asks what were the implications of these stories for the earliest generations of Christians, and what is their significance for Christians today.
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Bible; Bible -- Criticism, interpretation, etc; Resurrection -- Biblical teaching; Resurrection -- Biblical teaching; Bible ; New Testament ; Criticism, interpretation, etc; Resurrection ; Biblical teaching